Mechanisms Underlying Vascular Endothelial Growth Factor Receptor Inhibition–Induced Hypertension: The HYPAZ Trial. Issue 5 (29th March 2021) - Mäki-Petäjä, Kaisa M.; McGeoch, Adam; Yang, Lucy L.; Hubsch, Annette; McEniery, Carmel M.; Meyer, Paul A.R.; Mir, Fraz; Gajendragadkar, Parag; Ramenatte, Nicola; Anandappa, Gayathri; Santos Franco, Sara; Bond, Simon J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Drugs targeting the VEGF (vascular endothelial growth factor) signaling pathway are approved for several malignancies. Unfortunately, VEGF inhibitors lead to hypertension in 30% to 80% patients. Reduced nitric oxide synthase activity, microvascular rarefaction, and increased vascular resistance have been proposed as potential mechanisms. We aimed to assess these mechanisms in patients receiving the VEGF inhibitor, pazopanib, for cancer. Twenty-seven normotensive patients with advanced solid malignancies received pazopanib 800 mg od. Endothelial function was assessed using forearm plethysmography with intraarterial infusions of acetylcholine. Detailed hemodynamic measurements were taken. Density and diameter of the conjunctival and episcleral microvasculature were evaluated using hemoglobin video imaging. Measurements were taken at baseline, 2, and 12 weeks after initiation of pazopanib or earlier if patients became hypertensive. By the end of the trial, systolic blood pressure increased by 12 mm Hg (95% CI, 4–19 mm Hg; P =0.003), diastolic by 10 mm Hg (95% CI, 5–15 mm Hg; P <0.001), and peripheral vascular resistance by 888 dynes×s/cm 5 (95% CI, 616–1168 dynes×s/cm 5 ; P <0.001). Forearm blood flow improved: Ratio of acetylcholine response at end of trial/baseline was 2.8 (95% CI, 1.84–4.25; P <0.001). Microvascular density in the sclera was reduced by −15.5% (95% CI, −25.7% to −5.3%; P =0.003) and diameter by −2.09 µm (95% CI, −3.95 to −0.19 µm; P =0.03). A post hoc colorimetric assay revealed that pazopanib inhibited acetylcholinesterase activity by −56% (95% CI, −62% to −52%; P <0.001). Unexpectedly, pazopanib led to an increase in acetylcholine-mediated forearm blood flow response, likely due to the inhibition of acetylcholinesterase activity. Pazopanib increased peripheral vascular resistance and reduced microvascular density and diameter, suggesting that microvascular rarefaction could be one of the key mechanisms behind VEGF inhibition–induced hypertension. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01392352.